Motorcycle Related Injuries among Rural Dwellers in Irrua, Nigeria: Characteristics and Correlates. (20th October 2013) - Dongo, A. E.; Kesieme, E. B.; Eighemherio, A.; Nwokike, O.; Esezobor, E.; Alufohai, E.
Abstract : Background . The escalating use of motorcycle for commercial transportation of commuters and goods has resulted in an increase in morbidity and mortality from road traffic injuries. Objectives . To study the characteristics of motorcycle injuries seen in Irrua, Nigeria. Materials and Methods . This is a one-year prospective study of all patients seen from January 1, 2009, to December 31, 2009. A structured proforma was filled for all consecutive crash victims involving a motorcycle. Results . Motorcycle injuries accounted for 11.6% of attendance in surgical emergency room (142 out of 1, 214); 76.8% were males. Amongst victims 47.1% were riders, 42.9%, passengers, and 7.8% pedestrians. Extremity injury accounted for 42.2% while head injury occurred in 21.8%. There were 9 deaths (6.3%). In this study no victim used crash helmet. Conclusion . Banning of motorcycle for commercial use and the introduction of tricycles into rural/suburban comminutes may be an important preventive strategy.